From Linguistic-literary Inheritance Of Turkish Georgians - Saginadze, Rusudan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Majority of Georgian people living in different places outside the country is found in the nabourhood state, Republic of Turkey. We mean not only natives of Georgia, but olso those who were exiled to Turkey during the Muhajir period. Millions of Georgian people living in the territory of Turkey, are united under one common term “Chveneburebi” (meaning “of us”). They are also known as “Gurjebi”. Words containing the gurj base are toponyms – Gurjistan (Georgia), as well as – ethnonyms – Gurji (Georgian), and others – Gurjidili / Gurjije (Georgian Language). In general, Gurji is used in broad sense in Turkish Georgians’ speech: Gurji village, Gurji family, Gurji words, Gurji saying, Gurji school, Gurji name, Gurji Khorumi (dance)… It can also be found as the name determiner (Gurji Khatuni, Gurji Mekhmedi…) There are the verb forms as well in Georgian: gurjobs, but there is no word gurji nor the verb gurjobs in Georgian Language Vocabulary. There is only Gurjistan, which is defined as the country of Georgians – Georgia. Linguistic-Literary inheritance of Turkish Georgians is worth noticing. In the writings and stories of “Chveneburebi”, one can obviously see the connection with all the Georgian, striving for those depths they come from. Their folklore, legends, fairy tales, phrases, expressions… keep the Georgian language, beliefs on native land. The article implies the word forms, phrases, phraseologisms, in which faceicons of motherland, mother-tongue and – values of “Chveneburebi” are artistically, metaphorically expressed.